Phase I study of everolimus and mitomycin C for patients with metastatic esophagogastric adenocarcinoma. (2nd April 2013) - Werner, Dominique; Atmaca, Akin; Pauligk, Claudia; Pustowka, Anette; Jäger, Elke; Al‐Batran, Salah‐Eddin
Abstract This study aimed at determining the recommended dose of the mammalian target of rapamycin inhibitor everolimus in combination with mitomycin C (MMC) in patients with previously treated metastatic esophagogastric cancer. In this phase I trial, patients received escalated doses of oral everolimus (5, 7.5, and 10 mg/day) in combination with intravenous MMC 5 mg/m2 every 3 weeks. Endpoints were the dose‐limiting toxicity (DLT), safety, and response rates. Tumor tissues were tested for HER2‐status and mutations in the PTEN, PIK3CA, AKT1, CTNNB1, and E‐cadherin type 1 genes. Sixteen patients (12 male, four female) with gastric/gastroesophageal junction cancer were included. All patients were previously treated with a platinum‐based chemotherapy. Treatment cohorts were: 5 mg/day, three patients; 7.5 mg/day, three patients; and 10 mg/day, 10 patients. No DLTs occurred during dose escalation. Most frequent grade 3 toxicities were leukopenia (18.8%) and neutropenia (18.8%). All other grade 3 toxicities were below 10%. No grade 4 toxicities occurred. Three (18.8%) patients experienced partial responses and four patients had stable disease (SD). Antitumor activity according to Response Evaluation Criteria In Solid Tumors (RECIST)‐criteria was highest in the 10 mg/day cohort. No associations between HER2‐status or detected mutations and response were observed. The recommended dose of everolimus combined with MMC is 10 mg/day. Encouraging signs of antitumor activity were seen (http://www.ClinicalTrials.gov; Clinical trial registration number: NCT01042782).